Recent developments in alkene hydro-functionalisation promoted by homogeneous catalysts based on earth abundant elements: formation of C–N, C–O and C–P bond. Issue 27 (21st July 2015) - Rodriguez-Ruiz, Violeta; Carlino, Romain; Bezzenine-Lafollée, Sophie; Gil, Richard; Prim, Damien; Schulz, Emmanuelle; Hannedouche, Jérôme
<x xml:space="preserve">Abstract</x> This perspective provides an overview of the recent advancements in earth abundant element-based catalysts for alkene hydrofunctionalisation.